Heavy Hadronic Molecules Coupled with Multiquark States - Yamaguchi, Yasuhiro (2021)
We investigate the hidden-charm pentaquarks as a Λc͞D⁽*⁾ – Σc⁽*⁾͞D⁽*⁾ hadronic molecule coupling to a compact five-quark state. The coupling to the compact state leads to an hadron short-range interaction generating an attraction. In addition, the one pion exchange potential (OPEP) as a long-range interaction is introduced by the Lagrangians satisfying the chiral and heavy quark spin symmetries. The OPEP has been known as a driving force to bind atomic nuclei, where the tensor term leading the coupled-channel effect generates a strong attraction. The mass degeneracy of heavy hadrons due to the heavy quark spin symmetry enhances the OPEP derived by the πD⁽*⁾͞D⁽*⁾ and πΣc⁽*⁾Σc⁽*⁾ couplings. Introducing those interactions, we consistently explain the masses and widths of the Pc states reported by LHCb in 2019. The short range interaction has a dominant role to determine the energy-level structures, while the OPEP tensor term does the decay width.